Effects of intra- and interspecific competition on diet, growth and behaviour of Labeo calbasu (Hamilton) and Cirrhinus cirrhosus (Bloch) - Rahman, Mohammad Mustafizur; Verdegem, Marc (Elsevier B.V., 2010)
Effects of intra- and interspecific competition on diet, growth, grazing, swimming, resting and social behaviour of two carps calbasu (Labeo calbasu) and mrigal (Cirrhinus cirrhosus)were examined in single and mixed species treatments. Three treatments (tanks with 4 L. calbasu, 4 C. cirrhosus or 2 L. calbasu plus 2 C. cirrhosus) were andomly assigned to six 1m2 glass-walled aquaria, in which pond conditions were simulated. Overall, both species preferred feeding on benthic macroinvertebrates, spending the majority of its grazing time near the tank bottom. Intraspecific food competition affected L. calbasu more than interspecfic food competition. The opposite was true for C. cirrhosus which was more affected by L. calbasu than by intraspecific competition. L. calbasu broadened its selection of food items and increased grazing time in response to intense (intraspecific) food competition. This behaviour allowed L. calbasu to maintain its food intake and hence growth. In presence of L. calbasu, C. cirrhosus continued to feed mainly on benthic macroinvertebrates, not changing its feeding behaviour. Therefore, C. cirrhosus’ total food consumption and growth diminished in the presence of L. calbasu. In addition to food competition, direct interaction (interference competition from L. calbasu) also played an important role in the behaviour, diet, and growth rate of C. cirrhosus. From an ecological, economic and fish welfare point of view, it can be suggested that C. cirrhosus is deprived when cultured together with L. calbasu in aquaculture ponds.